Serum uric acid, kidney volume and progression in autosomal-dominant polycystic kidney disease - Helal, Imed (Oxford University Press, 2013)
BACKGROUND: Hyperuricemia has been implicated in the development and progression of chronic kidney disease, both in animal experiments and in clinical studies. As a potentially modifiable risk factor, we examined whether serum uric acid levels correlate with early hypertension, kidney volume and progression to end-stage renal disease (ESRD) in autosomal-dominant polycystic kidney disease (ADPKD). METHODS: Retrospective analysis of a prospective observational study of the natural history of ADPKD, conducted at the University of Colorado between 1985 and 2005. Included are 680 ADPKD adults who provided data on blood pressure, renal volume, renal function, uric acid, age at the onset of ESRD or last known age without ESRD. Serum uric acid levels were examined as a continuous variable and as gender-specific quartiles. The main outcome of interest was age at the onset of ESRD; secondary outcomes were hypertension onset before age 30 years and total kidney volume (TKV) at the study visit. RESULTS: Subjects with early-onset hypertension had higher age-adjusted serum uric acid levels than those with no or late-onset hypertension despite similar creatinine clearance. After adjusting for age, gender and creatinine clearance, there was a 5.8% increase in TKV and 4.1% increase in TKV/body surface area for every 1 mg/dL increase in uric acid (P = 0.007). The multivariate-adjusted Cox regression demonstrated a greater hazard ratio for ESRD for subjects in the 4th and 3rd quartiles of uric acid compared with the 1st [4.8 (2.6–8.9; P < 0.001) and 2.9 (1.6–5.3; P < 0.001)]. CONCLUSIONS: Higher serum uric acid levels are associated with earlier onset of hypertension, larger kidney volume and increased hazard for ESRD in ADPKD independent of gender, body mass index and renal function at the study visit. Randomized interventional studies will be necessary to examine whether treating hyperuricemia has a protective role in ADPKD.